Evaluation of anxiolytic effect of elaeocarpus ganitrus in mice (Health Renaissance, 2012)
Background: Antianxiety drugs are prescribed frequently and associated with several limitations factors that led to interest in the alternative remedies. Herbal drugs are used in developing and developed countries but there is lack of scientific evidence. Ayurvedic physician were used Elaeocarpus ganitrus for the treatment of mental calmness.Objectives: Evaluate the anxiolytic effect of Elaeocarpus ganitrus in mice.Methods: The experimental study was conducted with the extract of Elaeocarpus ganitrus in comparison with Diazepam 1mg/kg in 60 mice using open field test and passive avoidance apparatus in six experimental groups. The data were analyzed using Mann-Whitney test and P